Review of Situating language learning strategy use: Present issues and future trends; Editors: Zoe Gavriilidou, Lydia Mitits; Publisher: Multilingual Matters, 2021; ISBN: 9781788926713; Pages: 376 - Bielak, Jakub (Studies in Second Language Learning and Teaching, 2021)
Despite recently going through a sort of a crisis brought about by critical remarks made by eminent scholars (e.g., Dörnyei, 2005) about the raison d’être of the whole research area, the field of language learning/learner strategies (LLSs) is still very much alive and kicking. This is manifested by constant publication of meta-analyses (e.g., Plonsky, 2011), numerous journal articles, including state-of-the-art pieces (e.g., Pawlak, 2019), special issues of journals (e.g., Pawlak & Oxford, 2018) and books (e.g., Oxford, 2017), and the organization of a conference series (Situating Strategy Use [SSU]), all devoted exclusively to LLSs. The book under review here, Situating Language Learning Strategy Use: Present Issues and Future Trends, edited by Zoe Gavriilidou and Lydia Mitits, includes chapters originating in the talks delivered at the Second International Conference on SSU (Komotini, Greece, September 2017).